Pengaruh Psychological Capital terhadap Employee Engagement dengan Quality of Worklife sebagai Mediator - Hafilda Putri Iskandar; Muhammad Ilmi Hatta (UNISBA Press, 2022)
Abstract. This study aims to examine the effect of psychological capital on employee engagement with quality of work-life as a mediator variable at the BPJS Ketenagakerjaan West Java Company. The variable used in this study is Psychological Capital with the Psycap Questionnaire (PCQ) measuring instrument adapted from Luthans et al. (2007). The variable quality of work-life using the Walton model (1973) has been modified by Zin (2004). Employee engagement with the UWES-9 Scale measuring instrument adopted by Schaufeli & Bakker (2006). The proposed hypothesis is that there is an influence of psychological capital on the quality of work-life and employee engagement; there is an effect of quality of work-life on employee engagement; and quality of work-life mediates the effect of psychological capital on employee engagement. The subjects of this study were employees of the BPJS Employment Regional Office IV West Java and Bandung Branch Office, totaling 140 employees.The analysis technique used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) method. The results showed that there was a positive and significant effect of psychological capital on the quality of work-life. There is a positive and significant effect of psychological capital on employee engagement and employee engagement. The variable quality of work-life acts as a full mediation of the influence of psychological capital on employee engagement. Abstrak. Tujuan penelitian ini adalah untuk menguji pengaruh psychological capital terhadap employee engagement dengan quality of work-life sebagai variabel mediator pada Perusahaan BPJS Ketenagakerjaan Jawa Barat. Variabel yang digunakan dalam penelitian ini Psychological Capital dengan alat ukur Psycap Questionnaire (PCQ) yang diadaptasi dari Luthans et al. (2007). Variabel quality of work-life dengan alat ukur model Walton (1973) sudah dimodifikasi oleh Zin (2004). Employee engagement dengan alat ukur Skala UWES-9 yang diadopsi Schaufeli & Bakker (2006). Hipotesis yang diajukan adalah terdapat pengaruh psychological capital terhadap quality of work-life dan employee engagement; terdapat pengaruh quality of work-life terhadap employee engagement; dan quality of work-life memediasi pengaruh psychological capital terhadap employee engagement. Subjek penelitian ini karyawan Perusahaan BPJS Ketenagakerjaan Jawa Barat dan Kantor Cabang Bandung yang berjumlah 140 karyawan.Teknik analisis yang digunakan adalah Structural Equation Modeling (SEM) dengan metode Partial Least Square (PLS). Hasil penelitian menunjukkan terdapat pengaruh positif dan signifikan psychological capital terhadap quality of work-life dan employee engagement. Terdapat pengaruh positif dan signifikan quality of work-life terhadap employee engagement. Variabel quality of work-life berperan sebagai mediasi penuh pengaruh psychological capital terhadap employee engagement.